THE EFFECT OF INNOVATION AND ADVERTISING TO CUSTOMER LOYALTY AT CINEMAXX STUDIO IN MANADO - Aruperes, Loudy (JURNAL BERKALA ILMIAH EFISIENSI, 2015)
ABSTRACT Today, the competition in the business is getting tougher, the success of a company in achieving optimal synergy of performance is determined by how company was able to create a product or service that always follow trends in the market. The study aimsÂ  to find out the effect of innovation and advertising to customer loyalty at Cinemaxx Studio, Manado. 100 of Cinemaxx Studio, Manado customers were surveyed as respondents. Research show that variable innovation and advertising have significant positive effect on customer loyalty simultaneously, also advertising has significant and positive effect on customer loyalty partially, and variable innovation become strongest and dominant that impact to customer loyalty in this research, and advertising also have significant and positive impact to customer loyalty. As the recommendation, the company must still make innovation with their product and their must focus on the advertising to promoting their product to customers. Keywords: Innovation, Advertising And Customer Loyalty